Efek Anti-Mikrobial pada Ekstrak Cinnamomum verum (Kayu Manis) sebagai Terapi Adjuvant pada Malaria Falciparum - Khairun Nisa; Fitria Putridewi Abidin (CV. Jasa Sukses Abadi, 2021)
Malaria is a major public health problem in the world, especially in Indonesia. The prevalence of malaria in Indonesia reaches 6 percent with 2000 deaths each year, most of which are caused by Plasmodium falciparum. Various treatment options for falciparum malaria have been developed, but due to various factors, one of which is the adherence of patients who are not monitored medication, increases the risk of resistance to current malaria therapy. Therefore, the researchers conducted further research on alternative malaria therapies. Cinnamomun verum or cinnamon is known to contain cinnamaldehyde compounds which have antimicrobial properties. The purpose of this study was to determine the anti-microbial effect of Cinnamomun verum (cinnamon) extract as an adjuvant therapy in falciparum malaria. This literature review article takes 25 case report articles, research articles, and literature reviews. The conclusion of this study is that the cinnamaldehyde compound in the extract of Cinnamomun verum has an antiparasitic effect which can inhibit the denaturation potential of amino acids, inhibits β-hematin formation and activity of the reductase enzyme on Plasmodium falciparum enoyl-ACP reductase. It is known that these four things have an important role in the pathogenesis of falciparum malaria.